Analisis Pengembangan Pariwisata di Kecamatan Binuang Kabupaten Polewali Mandar - Andi Lukman Irwan; Juanda Nawawi; Ayu lia (Departemen Ilmu Pemerintahan Fisip Unhas, 2021)
This study aims to determine the role of the government in tourism development in the Binuang sub-district, Polewali Mandar Regency, seen from the arrangement and development of tourist objects, the development and development of tourism supporting facilities and infrastructure and the promotion of tourism. The method used in this research is to use a qualitative descriptive research type which aims to describe the problem solving of the research object based on visible facts or data in the field. Data collecting technique is done by interviewing and observing and documentation which includes archives, literature review or literature related to research problems. The results showed: tourism development in Binuang Subdistrict, Polewali Mandar Regency, seen from the arrangement and development of tourist objects in accordance with the Regional Tourism Development Master Plan by identifying tourist objects that have the potential to focus on development. In addition, coaching activities for tourism managers are also carried out every few months in order to improve the quality and quality of tourism objects. Then, the development and development of tourism facilities and infrastructure carried out by the government can also be seen from the development and maintenance efforts of tourism supporting facilities and infrastructure. Tourism promotion by the Youth Sport and Tourism Agency which is considered quite effective is the Polewali Mandar Festival Fork & Art (PIFAF) which in addition to introducing culture also introduces tourism potentials in Polewali Mandar Regency.